A mathematical modeling approach to improve the point estimation of landfill gas surface emissions using the flux chamber technique. Issue 6 (1st November 2002) - Perera, M D.N; Hettiaratchi, J P.A; Achari, G
Abstract : The accurate determination of gas emissions from sanitary landfills is necessary to assess the contribution of landfill gas emissions to global warming and to develop optimum techniques to control emissions from individual landfills. The most popular method available for point measurement of landfill gas, the closed or static flux chamber technique, has inaccuracies associated with the technique itself. A new mathematical modeling approach is presented to estimate the errors caused by changes to the flow pattern of gases within the soil cover when a closed flux chamber is placed on top of the cover to measure gas emissions. The proposed two-dimensional numerical model considers both advective and dispersive processes of gas migration. The model was calibrated and verified using data from controlled laboratory experiments. The model was able to predict the fluxes with 95% accuracy. Based on laboratory experiments and model predictions, our analysis showed that a closed flux chamber technique would underestimate actual gas flux by as much as 65% depending on the configuration of the flux chamber, the actual flux rate, and the characteristics of the soil in the landfill cover. Key words : landfill gas, methane, global warming, mathematical modeling, landfill cover, simulation, environmental monitoring, flux chamber.